Alu recombination-mediated structural deletions in the chimpanzee genome. - Kyudong Han; Jungnam Lee; Thomas J Meyer; Jianxin Wang; Shurjo K Sen; Deepa Srikanta; Ping Liang; Mark A Batzer (PLoS Genetics, 2007)
With more than 1.2 million copies, Alu elements are one of the most important sources of structural variation in primate genomes. Here, we compare the chimpanzee and human genomes to determine the extent of Alu recombination-mediated deletion (ARMD) in the chimpanzee genome since the divergence of the chimpanzee and human lineages ( approximately 6 million y ago). Combining computational data analysis and experimental verification, we have identified 663 chimpanzee lineage-specific deletions (involving a total of approximately 771 kb of genomic sequence) attributable to this process. The ARMD events essentially counteract the genomic expansion caused by chimpanzee-specific Alu inserts. The RefSeq databases indicate that 13 exons in six genes, annotated as either demonstrably or putatively functional in the human genome, and 299 intronic regions have been deleted through ARMDs in the chimpanzee lineage. Therefore, our data suggest that this process may contribute to the genomic and phenotypic diversity between chimpanzees and humans. In addition, we found four independent ARMD events at orthologous loci in the gorilla or orangutan genomes. This suggests that human orthologs of loci at which ARMD events have already occurred in other nonhuman primate genomes may be "at-risk" motifs for future deletions, which may subsequently contribute to human lineage-specific genetic rearrangements and disorders.